Regulating of wear properties through microstructure engineering in novel cost-effective Fe30Ni25Cr25Mo10Al10 high-entropy alloy processed by cyclic closed-die forging - Majid Naseri; Alena Myasnikova; Davood Gholami; Omid Imantalab; Dmitry Mikhailov; Mostafa Amra; Nataliya Shaburova; Milena Efimova; Aleksandr Orlov; Seyedmehdi Hosseini; Yong-Cheng Lin; Abdel-Hamid I. Mourad; et al. (Journal of Alloys and Metallurgical Systems, 2024)
This study presents a novel cost-effective Fe30Ni25Cr25Mo10Al10 high-entropy alloy with a dual-phase microstructure that was processed using cyclic closed-die forging (CCDF) at room temperature for a maximum of six passes. The as-homogenized alloy exhibited [CrMoFe]-rich dendrites with dual-size morphology dispersed in an almost uniform face-centered cubic (FCC) matrix. It was found that as the number of CCDF passes increased, leading to a more homogenous nanograin, there was an accumulation of dislocations, fragmentation of [CrMoFe]-rich dendrites, and enhanced distribution within the matrix. These conditions were conducive to the creation of a nanostructured Fe30Ni25Cr25Mo10Al10 alloy with superior mechanical properties. Texture analysis indicated that the prominent texture components for the Fe30Ni25Cr25Mo10Al10 alloy after six passes were Rotated Cube {001}<110>, S {123}<634>, and Dillamore {4 4 11}<11 11 8>. After the sixth CCDF pass, the Fe30Ni25Cr25Mo10Al10 alloy exhibited the highest microhardness (∼ 974 HV) and the lowest wear rate (∼ (0.8 ± 0.1) × 10–5 mm3.N−1.m−1). Additionally, it was proposed that the development of the Rotated Cube {001}<110> texture component contributed positively to enhancing wear resistance in the cost-effective high-entropy alloys. Considering the obtained results, it is reasonable to propose that CCDF processing is significant potential for the advancement of cost-effective nanostructured high-entropy alloys for industrial applications.